An improved methodology for obtaining soil hydraulic properties by laboratory evaporation experiments - Inforsato, Leonardo (2023)
Among the methods for determining the soil hydraulic properties, the laboratory evaporation experiment is distinguished due to its experimental easiness and the simultaneous acquisition of the soil water retention function, (h), and conductivity function, K(h). This thesis aims to improve the quality of the obtained parameters of the conductivity and retention functions using data measured in such evaporation experiments. It consists of three chapters (I, II, and III) with the respective specific objectives: (1) extension of the validity of the retention and conductivity models to the dry range of pressure heads; (2) improvement in the estimation of the K(h) function when using the simplified evaporation method and (3) evaluating parameter transforms for the mathematical expressions of s-shaped retention functions improving the uncertainty of the fitted parameters. With the results obtained in chapter I, it is possible to extend the validity of tested and conceptualized models without the need to change or reassess the known hydraulic parameters. Results from chapter II allow obtaining values of the conductivity function with greater exactness, mainly in Sandy textured soils, where the simplified evaporation method showed to be less accurate. Chapter III elaborates on the reduction of uncertainties in hydraulic parameters determined by non-linear fitting through parameter transformation of the hydraulic properties